The Influence of Health Education on Public Knowledge about Sports Accidents - Sugiharto, Firman; Asmara, A Danang; Sari, Wulan Puspita; Freitas, Lurdes A; Ramdani, Dadan; Anna, Anastasia; Nuraeni, Aan (Universitas Padjadjaran, 2025)
Sports accidents can have a very significant impact on various aspects of life. However, public knowledge regarding this still needs to be improved and uneven, so it is essential to disseminate information related to preventing and handling sports accidents. This study aimed to determine the effect of health education on public knowledge in the prevention and early handling of sports accidents. This study was a pre-experimental study with a one-group pre-post-test approach. The research sample consisted of 230 respondents and was conducted using an accidental sampling technique. Data analysis was done by looking at the difference in pre-test and post-test values using the Wilcoxon difference test. The results of the study showed that before health education was given, the average value of respondents' knowledge was 59.30 ± 26.21.Meanwhile, after being given health education, the average score increased to 84.87 ± 20.27. Bivariate analysis showed a statistically significant difference with a p-value <0.001. This shows a difference in public knowledge about sports accidents before and after being given health education. There is a need for activities like this to be carried out in other communities and society in general so that the dissemination of information and public understanding related to sports accidents will improve and the impact of delays in handling injuries can be minimized. Keywords: Health education; knowledge; sports accidents.